Bridging Narratology, Ethnology, and Semiotic: A New Naratoethnosemiotic Framework for Reconstructing Banjar Identity in Local Fiction by Jamal T. Suryanata - Kamal Hasuna; Heppy Lismayanti (Tabasa: Jurnal Bahasa, Sastra Indonesia, dan Pengajarannya, 2026)
Banjar ethnic identity is increasingly subject to erosion as a consequence of modernisation and globalisation; however, it continues to be preserved and articulated within local literary expressions. To address a significant gap in the literature, which has largely examined Banjar literary works through single analytical lenses, this study introduces a novel, integrative "naratoethnosemiotic" framework. This framework systematically combines narratology (Currie), theories of ethnic identity (Hall), and semiotic analysis (Barthes and Fairclough) to provide a more comprehensive understanding of cultural representation. This study aims to examine the representation of Banjar ethnic identity in three fictional works by Jamal T. Suryanata: Galuh, Pambatangan, and Parangmaya. A qualitative methodology with a phenomenological approach was employed to explore these dimensions. Data were collected through translation, identification, classification, hermeneutic interpretation, and conclusion drawing, with validity ensured by triangulation and expert auditing. The results show that the structure of Banjar fiction comprises narrative representation (behaviour, expression, and context), point of view (character thoughts and event chronology), and character traits (behaviour). Banjar ethnic identity is articulated through five principal domains of cultural values—relationships with God, nature, others, society, and the self-alongside expressions of local wisdom, including knowledge systems, values, skills, beliefs, and decision-making processes. The analysis of cultural discourse demonstrates multilayered meanings, encompassing denotative and connotative signs, culturally embedded myths (e.g., pamali and batatamba), underlying ideological constructs, and broader socio-cultural contexts. The findings indicate that Banjar fiction serves as a significant medium for the preservation and transmission of ethnic identity. The primary contribution of this research lies in its provision of an evidence-based, interdisciplinary framework that not only deepens scholarly understanding but also offers practical guidance for educators, local authors, and policymakers in leveraging Banjar literature for cultural preservation.    Identitas etnik Banjar saat ini menghadapi erosi akibat modernisasi dan globalisasi, namun masih terpelihara dalam karya sastra lokal. Untuk mengatasi kesenjangan penelitian yang signifikan, di mana karya sastra Banjar sebagian besar dikaji melalui pendekatan tunggal, penelitian ini memperkenalkan kerangka "naratoetnosemiotika" yang baru dan integratif. Kerangka ini secara sistematis menggabungkan naratologi (Currie), teori identitas etnik (Hall), dan analisis semiotika (Barthes & Fairclough) untuk memberikan pemahaman yang lebih komprehensif tentang representasi budaya. Penelitian ini bertujuan untuk mengungkap identitas etnik Banjar dalam tiga fiksi karya Jamal T. Suryanata: Galuh, Pambatangan, dan Parangmaya. Metode kualitatif dengan pendekatan fenomenologis digunakan. Data dikumpulkan melalui penerjemahan, identifikasi, klasifikasi, interpretasi hermeneutik, dan penarikan simpulan, dengan validitas yang dijamin melalui triangulasi dan auditor ahli. Hasil penelitian menunjukkan bahwa struktur fiksi Banjar terdiri atas representasi naratif (tingkah laku, ekspresi, konteks), sudut pandang (pemikiran tokoh, kronologi peristiwa), dan karakter tokoh (sifat, perilaku). Identitas etnik Banjar direpresentasikan melalui lima nilai budaya (hubungan dengan Tuhan, alam, sesama, masyarakat, dan diri sendiri) serta kearifan lokal (pengetahuan, nilai, keterampilan, kepercayaan, pengambilan keputusan). Makna wacana budaya meliputi tanda denotatif/konotatif, mitos (pamali, batatamba), ideologi, dan konteks sosial. Penelitian menyimpulkan bahwa fiksi Banjar berperan sebagai medium pelestarian identitas etnik. Kontribusi utama penelitian ini adalah menyediakan kerangka kerja interdisipliner berbasis bukti yang tidak hanya memperdalam pemahaman ilmiah tetapi juga menawarkan panduan praktis bagi para pendidik, penulis lokal, dan pembuat kebijakan dalam memanfaatkan sastra Banjar untuk pelestarian budaya.